2021
DOI: 10.1097/md.0000000000027217
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness and safety of Chuna manual therapy adjuvant to Western medicine in patients with chronic obstructive pulmonary disease

Abstract: Background In chronic obstructive pulmonary disease (COPD) management, greater emphasis has been placed on symptomatic improvement and enhanced quality of life in patients. Manual therapy among respiratory rehabilitation programs has received much attention recently, with the publication of numerous studies. In South Korea, a method known as Chuna Manual Therapy (CMT) has been applied in the management of COPD patients and in clinical practice, but the clinical basis for safety and effectiveness is yet to be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The CMT intervention was administered once a week for 8 weeks, and assessments were performed at baseline and after 4, 8, and 12 weeks of intervention. The protocol has already been published [21] and a flow diagram of the study is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CMT intervention was administered once a week for 8 weeks, and assessments were performed at baseline and after 4, 8, and 12 weeks of intervention. The protocol has already been published [21] and a flow diagram of the study is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…The CMT intervention was administered once a week for 8 weeks, and assessments were performed at baseline and after 4, 8, and 12 weeks of intervention. The protocol has already been published [21] and a flow diagram of the study is shown in Figure 1. showing a forced expiratory volume in 1 s (FEV1)/forced vital capacity (FVC) ratio of <0.70 [4] and currently undergoing standard drug therapy 3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation